The Level of Knowledge about Sensory Integration disorder by Specialists In Children with Autism Spectrum - Alrefaay , Alia; Abo Hasan , Fadia (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The aim of this study is to identify the the level of knowledge about the appearances of sensory integration disorder by Specialists who working with autistic children , who have master in many specializations (special education, speech and language , psychomotor) in some center for rehabilitation in Damascus , and the relationship with the specialization, and the number of years of teaching experience. The sample consisted of (15) Specialists of special education, (15) Specialists of speech and language ,(10) Specialists of psychomotor. The researcher developed a questionnaire to Achieve the aims of this study, the questionnaire was consisting of (70) items distributed on (6) domains (proprioception system disorder, vestibular system disorder, tactile system disorder, Auditory system Disorder, Visual system Disorders, Olfactory and tasting system disorder) The results of the study indicate that the level of possessing knowledge about the appearances of sensory integration disorder by Specialists was low on the some of sub-dimensions of the questionnaire and medium on the other sub-dimensions of the questionnaire, and medium on the questionnaire as a whole,. The results also indicated that there are statistically significant differences between the average degrees of Specialists on the questionnaire as a whole according to specialization in favor psychomotor, and there are no statistically significant differences according to number of years of teaching experience.